Is a biomarker-based diagnostic strategy for invasive aspergillosis cost effective in high-risk haematology patients?. (28th January 2017) - Macesic, N.; Morrissey, C.O.; Liew, D.; Bohensky, M.A.; Chen, S.C.-A.; Gilroy, N.M.; Milliken, S.T.; Szer, J.; Slavin, M.A.
Abstract: Empirical antifungal therapy is frequently used in hematology patients at high risk of invasive aspergillosis (IA), with substantial cost and toxicity. Biomarkers for IA aim for earlier and more accurate diagnosis and targeted treatment. However, data on the cost-effectiveness of a biomarker-based diagnostic strategy (BDS) are limited. We evaluated the cost effectiveness of BDS using results from a randomized controlled trial (RCT) and individual patient costing data. Data inputs derived from a published RCT were used to construct a decision-analytic model to compare BDS ( Aspergillus galactomannan and PCR on blood) with standard diagnostic strategy (SDS) of culture and histology in terms of total costs, length of stay, IA incidence, mortality, and years of life saved. Costs were estimated for each patient using hospital costing data to day 180 and follow-up for survival was modeled to five years using a Gompertz survival model. Treatment costs were determined for 137 adults undergoing allogeneic hematopoietic stem cell transplant or receiving chemotherapy for acute leukemia in four Australian centers (2005–2009). Median total costs at 180 days were similar between groups (US78, 774 for SDS [IQR US50, 808–123, 476] and US81, 279 for BDS [IQR US59, 221–123, 242], P = .49). All-cause mortality was 14.7% (10/68) for SDS and 10.1% (7/69) for BDS, ( P = .573). The costs per life-year saved were US325, 448, US81, 966, and US3, 670 at 180 days, one year and five years, respectively. BDS is not cost-sparing but is cost-effective if a survival benefit is maintained over several years. An individualized institutional approach to diagnostic strategies may maximize utility and cost-effectiveness.